2014
DOI: 10.1242/dev.111898
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary changes in TGFα distribution underlie morphological diversity in eggshells from Drosophila species

Abstract: Drosophila eggshells display remarkable morphological diversity among species; however, the molecular origin of this structural diversification is mostly unknown. Here, we analyzed the dorsal ridge (DR), a lumen-like structure along the dorsal side of eggshells, from numerous Drosophila species. This structure varies in length and width across species, and is absent from D. melanogaster eggshells. We associated DR formation with distinct spatiotemporal changes in epidermal growth factor receptor (EGFR) activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…Species with a dorsal ridge exhibit an unusual staining pattern at stage 10 for diphosphorylated ERK (dpERK), a marker for EGFR signaling. In many species, dpERK is confined to the dorsal anterior region, where the midline and appendage cell types will be specified, but in species with a dorsal ridge, dpERK extends more posteriorly, along the dorsal midline (Niepielko and Yakoby, 2014). The dorsal midline is located over the path the nucleus would be expected to traverse as it moves from the posterior of the oocyte, during early oogenesis, to the dorsal anterior, where it resides in mid and late oogenesis.…”
Section: Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Species with a dorsal ridge exhibit an unusual staining pattern at stage 10 for diphosphorylated ERK (dpERK), a marker for EGFR signaling. In many species, dpERK is confined to the dorsal anterior region, where the midline and appendage cell types will be specified, but in species with a dorsal ridge, dpERK extends more posteriorly, along the dorsal midline (Niepielko and Yakoby, 2014). The dorsal midline is located over the path the nucleus would be expected to traverse as it moves from the posterior of the oocyte, during early oogenesis, to the dorsal anterior, where it resides in mid and late oogenesis.…”
Section: Evolutionmentioning
confidence: 99%
“…Indeed, grk knockdown by RNAi inhibits dorsal ridge formation in D. willistoni , a species that normally produces this structure. Strikingly, expressing the D. willistoni Grk protein (wGRK) in D. melanogaster not only rescues a grk mutant, but it can also cause the formation of a partial dorsal ridge (Niepielko and Yakoby, 2014). These exciting findings raise the question of how differences in Grk between D. willistoni and D. melanogaster control this aspect of morphology; possibilities may include differences in signal strength, or in ligand anchoring or stability (Niepielko and Yakoby, 2014).…”
Section: Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other situations, however, ligand concentration, not the identity of the ligand itself, determines the developmental outcome (Austin et al 2014). Previous studies using genomic regions to rescue grk null mutants showed that expression of Drosophila willistoni grk in D. melanogaster can induce an ectopic dorsal ridge structure in eggshells (Niepielko and Yakoby 2014). Unfortunately, the available scaffold in S. lebanonensis (Vicoso and Bachtrog 2015) lacks potentially important upstream and downstream regulatory regions, and we were unable to bridge the gap with the flanking genes predicted by synteny, D12 and AKAP200 .…”
Section: Resultsmentioning
confidence: 99%
“…1F) (32,36) In contrast to D. melanogaster, which lacks the dorsal ridge and is patterned by GRK localized around the oocyte nucleus (Fig. 4E), D. willistoni is patterned by the GRK profile that is significantly extended toward the posterior end of the follicular epithelium (45) (Fig. 4F).…”
Section: From D Melanogaster To Other Speciesmentioning
confidence: 97%